2023
DOI: 10.1001/jamapsychiatry.2023.1179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Disruptive Life Events for Individuals Diagnosed With Schizophrenia or Bipolar I Disorder Using Data From a Consumer Credit Reporting Agency

Abstract: ImportanceThere is a dearth of population-level data on major disruptive life events (defined here as arrests by a legal authority, address changes, bankruptcy, lien, and judgment filings) for patients with bipolar I disorder (BPI) or schizophrenia, which has limited studies on mental health and treatment outcomes.ObjectiveTo conduct a population-level study on disruptive life events by using publicly available data on disruptive life events, aggregated by a consumer credit reporting agency in conjunction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These citations were focused on statistical analysis. Another publication linked a credit history report to identify serious nancial events in patients' lives, such as bankruptcy [35]. One more citation utilized the interview format for events identi cation and compared them to what was documented in EHR and found that health records "generally failed to include social contexts salient to patients" [36].…”
Section: Resultsmentioning
confidence: 99%
“…These citations were focused on statistical analysis. Another publication linked a credit history report to identify serious nancial events in patients' lives, such as bankruptcy [35]. One more citation utilized the interview format for events identi cation and compared them to what was documented in EHR and found that health records "generally failed to include social contexts salient to patients" [36].…”
Section: Resultsmentioning
confidence: 99%
“…One more citation utilized the interview format for events identi cation and compared them to what is documented in EHR and found that health records "generally failed to include social contexts salient to patients" [29]. Another publication linked a credit history report to identify serious nancial events in patients' lives, such as bankruptcy [30]. One citation [31] discussed issues of using external data sources linked to EHR for capturing " nancial, legal, life event and sociodemographic data" to improve suicide screening models.…”
Section: Resultsmentioning
confidence: 99%
“…These citations were focused on statistical analysis. Another publication linked a credit history report to identify serious financial events in patients’ lives, such as bankruptcy [ 35 ]. One more citation utilized the interview format for events identification and compared them to what was documented in EHR and found that health records “generally failed to include social contexts salient to patients” [ 36 ].…”
Section: Resultsmentioning
confidence: 99%